2014
DOI: 10.2807/1560-7917.es2014.19.26.20843
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spread of the novel respiratory syncytial virus A ON1 genotype, central Italy, 2011 to 2013

Abstract: Respiratory infections positive for human respiratory syncytial virus (RSV) subtype A were characterised in children admitted to hospitals in Rome and Ancona (Italy) over the last three epidemic seasons. Different strains of the novel RSV-A genotype ON1, first identified in Ontario (Canada) in December 2010, were detected for the first time in Italy in the following 2011/12 epidemic season. They bear an insertion of 24 amino acids in the G glycoprotein as well as amino acid changes likely to change antigenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
87
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 35 publications
13
87
2
1
Order By: Relevance
“…In 2010, an NA1 variant with a 72 nucleotide duplication in HVR2 was identified in Ontario, Canada (genotype ON1) (203,207). ON1 and similar NA1 variants with the large duplication have since been reported worldwide, although they have yet to replace GA2, NA1 and GA5 in the population (192,194,195,197,198,202,203,215,216).…”
Section: Genetic Diversitymentioning
confidence: 99%
See 4 more Smart Citations
“…In 2010, an NA1 variant with a 72 nucleotide duplication in HVR2 was identified in Ontario, Canada (genotype ON1) (203,207). ON1 and similar NA1 variants with the large duplication have since been reported worldwide, although they have yet to replace GA2, NA1 and GA5 in the population (192,194,195,197,198,202,203,215,216).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…However, it has been suggested that successful new genotypes may possess novel antigenicity and thus ability to evade host immunity, resulting in hospitalisation spikes on introduction to a naive population, such as associated with the emergence of ON1, without an inherent ability to cause more severe disease (197,201). This hypothesis is consistent with the increases in hospital and ICU admissions associated with ON1 compared to other RSV strains (197,198), and the large epidemics associated with NA1 and NA2 when they first emerged in Japan in the mid 2000s but not observed since (201 (227). Antibiotic resistance is a growing problem with many bacterial pathogens, and resistance has been observed in S. pneumoniae to both first-and second-line antibiotics commonly used to treat bacterial pneumonia (75)(76)(77)81).…”
Section: Genetic Diversitymentioning
confidence: 99%
See 3 more Smart Citations